Daya Hambat Ekstrak Biji Ketumbar (Coriandrum Sativum L) Terhadap Pertumbuhan Bakteri Shigella Dysenteriae Metode Cakram - Nur Hasanah; Rovika Sovia Dori (STIKes Kharisma Persada, 2019)
Coriander seed (Coriandrum Sativum l.) is a plant that originated in the Mediterranean, and the Middle East, Indonesia society generally in stead right as a condiment Cook. Coriander seed is often also used for diabetes, diuretic, hypolipidemia, anti-fungal, bacterial or yeast either antibiotic, antioxidan, and anti-inflammatory. Extraction of coriander seeds is carried out by means of maceration using solvent ethanol 70%. The current concentration of 50% used, 75%, and 100%, with positive control (cotrimoxazole 5 µ g/50 µ l) and negative control (aquadest sterile). The test is performed twice with disc diffusion method of repetition. Phytochemical screening extracts of coriander seeds showed the presence of compounds alkaloids, saponins, tannins, flavonoids, phenolic, Triterpenoid, and glycosides. The test results showed that extracts of coriander seeds capable of inhibiting growth bacteria shigella dysenteriae. Coriander seed extract which is able to inhibit the growth of bacteria of the shigella dysenteriae is the concentration of 100% and an average of 8.7 mm in diameter with drag power belongs belongs to the medium.